Young consumers' considerations of healthy working conditions in purchasing decisions: a qualitative examination. Issue 5 (4th May 2017) - Dixon, Shane M.; Nordvall, Anna-Carin; Cukier, Wendy; Neumann, W. Patrick
Abstract: Research has suggested that products manufactured under healthy work conditions (HWC) may provide a marketing advantage to companies. This paper explores young consumers' considerations of HWC in purchasing decisions using data from qualitative interviews with a sample of 21 university students. The results suggest that interviewees frequently considered the working conditions of those who produced the products they purchased. Participants reported a willingness to pay 17.5% more on a 100 product if it were produced under HWC compared to not. Their ability and willingness to act on this issue was, however, hampered by a lack of credible information about working conditions in production, the limited availability of HWC goods and a presumed higher price of HWC goods. While caution should be applied when generalising from this targetable market segment to a general population, these results provide actionable direction for companies interested in using a HWC brand image to gain a strategic sales advantage. Practitioner Summary: This interview study shows that young consumers are interested in, and willing to pay a premium for, goods made under healthy working conditions (HWC). Reported barriers to acting on this impulse include a lack of credible information on working conditions. Ergonomics can help provide a strategic marketing advantage for companies.